Case study analysis on Department of Science and Technology (DOST) Small Enterprise Technology Upgrading Program Innovation Support System Support Fund (SETUP ISSF) among Food Sector Beneficiaries in the Province of Aklan - Lachica, Jairus M.; Posadas, Roger D. (Quezon City University of the Philippines Diliman, 2014)
The Department of Science and Technology has implemented various programs in the Philippines. One of the programs is the Small Enterprise Technology Upgrading Program (DOST SETUP) which assists SMEs in improving productivity and competitiveness through the infusion of advanced technologies, technology acquisition, manpower trainings, consultancy services, technical assistance, packaging and labelling services, product testing and database information systems. In Region VI, there are a total of 163 firms which have been assisted under the DOST SETUP Innovation System Support Fund from 2003-2012 wherein 12 firms were engaged in the food processing sector that had availed the program in the province of Aklan. To assess the project implementation among food sectors, a case study was conducted to better understand the things that affect the success and failure of their project under DOST SETUP ISSF in the province of Aklan. In this study, the project researcher aimed in investigating the projects being implemented and those that have already been implemented by DOST VI under SETUP ISSF within the food processing sector in the province of Aklan. This will determine how the food processing firms managing the project consider it to be a success or a failure. Also, the case study will identify the factors to be considered in project implementation amongst food processors in the province. Specifically, the study will identify the enterprise profile of food processing firms who availed the program, identify problems encountered and solutions performed by the firm during project implementation, determine the factors that affect the success and failure of projects and assess project implementation of each firm. The results of the study will give information to the Department of Science and Technology Region VI (DOST VI) on important areas to be enhanced or developed for the continual progress of the program, not only for the food processing sector but also to other priority areas of DOST. Also, this will provide information about factors that can be critical to the success of a project to the implementing agency as well as the beneficiary. Further, this will help them determine any appropriate technology needed in the production and identify factors that will affect the project implementation for prevention and adjustment to project operation. The study utilized a case study research. This will provide more thorough analysis of a situation or case which might reveal interesting information about that particular classification of conditions. The participants were the 13 SETUP ISSF food processing beneficiaries from 2003-2012 in the province of Aklan. At the end of the project, the project researcher will create an updated list of the status of DOST SETUP ISSF beneficiaries as grouped by the food processing sector; determine the factors that affect the success and failure of project implementation; assess DOST SETUP ISSF impact among food processing beneficiary in the province of Aklan; and identify areas needed for improvement to further strengthen the implementation of DOST SETUP ISSF in the region.
In partial fulfillment of the requirements in TM 299
Thesis
Keywords: Department of Science and Technology (DOST); Small business -- Philippines; Food industry and trade -- Philippines; Small enterprise technology upgrading program innovation support system support fund (SETUP ISSF).